EXTRACTION AND PURITY DNA OF Culex spp MOSQUITO IN KEMELAK VILLAGE, BINDUNG LANGIT, OGAN KOMERING ULU - Nuriessa Aputri, Farah; Hanum, Laila; Safitri, Ayu; Windusari, Yuanita (BIOVALENTIA: Biological Research Journal, 2021)
Culex spp are mosquito vectors that have a very wide distribution capability and are carriers of pathogens that can interfere with human and animal health. The wide distribution makes Culex spp a dangerous threat. DNA extraction is one of the important steps in obtaining genetic information and genetic analysis. Good quality DNA is used for activities such as the use of molecular markers, genome library creation, and sequencing. This study aims to determine the quality, concentration and purity of Culex spp mosquito DNA in Kemelak Bindung Langit Village, OKU Regency. It is hoped that the sample can be used for further research analysis on Mitochondria D-Loop Sequences in Culex spp mosquitoes. Quantitative measurement of DNA in the form of concentration and purity of DNA using Nanodrop Thermo cycle while qualitative DNA using electrophoresis technique. The results of the isolation of the mosquito genome DNA, obtained clear DNA bands without any degradation (smear) and the concentration results for the four samples ranged from 10-100 ng/ÂµL and the DNA purity was good, ranging from 1.8 to 2.00.